The Role of Arabic Linguistics in the Development of Modern Linguistic Theory - Adittia Batalipu; Widiya Ayuningsi Retno Anggraini (Faculty of Education and Teacher Training, 2026)
This study aims to explore the role of Arabic linguistics in the development of modern linguistic theory through an in-depth analysis of the traditions and intellectual contributions of classical Arabic linguists. Using a descriptive qualitative approach, this study involves three main stages: data collection from primary and secondary literature, critical analysis of Arabic linguistic theories, and synthesis and interpretation of the results to identify their relevance to contemporary linguistics. The results indicate that Arabic linguistics has made significant contributions in several areas, such as phonology through the analysis of points and modes of articulation; syntax and semantics through Al-Jurjani’s nazm theory; and pragmatics through the balaghah approach, which emphasizes social context and communicative intent. Furthermore, the holistic approach of Arabic linguistics—which integrates phonology, morphology, syntax, semantics, and aesthetics—enriches modern linguistic insights, which tend to be fragmented. Intellectual transfer through the translation of works by Arabic linguists into Latin also served as the foundation for the development of linguistics in medieval Europe. This study concludes that the Arabic linguistic tradition not only influenced modern linguistic theories but also offers innovative approaches that remain relevant to this day. These findings underscore the importance of exploring the relationship between classical and modern scholarly traditions to understand the complexity of language in a more holistic manner.